Overcoming Communication Barriers to Healthcare for Culturally and Linguistically Diverse Patients - Li, EdD, Chieh; Abdulkerim, MA, Noora Son, BA; Jordan, BS, Cara A.; Son, BA, Christine Ga Eun (North American Journal of Medicine and Science, 2017)
The growing diversity in the United States brings with it multiple cultures, languages, and communication styles. Effective communication between healthcare providers and patients is essential for quality healthcare. Barriers to communication contribute to health disparities among racial/cultural minority groups. In this article, we analyzed both verbal and nonverbal barriers to effective communication with Limited English Proficiency (LEP) patients, including issues with using interpreters. Following the analysis, we explored strategies to overcome the barriers at systemic and individual levels. The available literature indicates that most of the legislative initiatives took place in three domains: (1) continuing education on serving LEP patients for health professionals, (2) certification of healthcare interpreters, and (3) reimbursement for language services for Medicaid/SCHIP enrollees. Additional strategies recommended by previous studies include (4) informing all LEP patients about their legal rights, the resources available to them, and the actions they can take when these are not enforced or made accessible. We proposed adding two more strategies: (5) increasing awareness of both verbal and nonverbal (proxemics, kinesics and paralanguage) barriers to cross-cultural communication, and (6) increasing multicultural competencies of health providers. [N A J Med Sci. 2017;10(3):103-109. DOI: 10.7156/najms.2017.1003103]